Mendalami Makna Tafsir Yusuf terhadap Mimpi Firaun dari Bingkai Kaum Pentakostal - Manurung, Kosma (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Abstract: The dream of Pharaoh, the ruler of the world at that time, turns out to be the way in for a young man named Joseph to fulfill God's purpose in his life. Yusuf, who was a teenager from a shepherd family, was in the process of becoming the second most powerful person in a superpower country and the most advanced in civilization at that time and in that very place Joseph saw the dream that God had placed fulfilled, through the entrance telling the dream of Pharaoh, the ruler of the world at that time. This study examines the deeper meaning of Joseph's interpretation of Pharaoh's dream in Genesis 41 from the perspective of the Pentecostals. The selection of qualitative methods with the approach of text analysis and literature review is expected to be able to provide a strong, systematic, and careful explanation of the story of Joseph's life as described in the Bible, an analysis of Pharaoh's dream interpretation in Genesis 41, and the meaning of the Pentecostal frame regarding this story. It was concluded that for Pentecostals, the interpretation of Pharaoh's dream by Joseph is a story which shows that God designed the most perfect, Joseph who lived God's purpose, divine solution, and God's means to fulfill his purpose in Joseph's life. Abstrak: Mimpi Firaun sang penguasa dunia waktu itu ternyata merupakan jalan masuk seorang anak muda bernama Yusuf untuk mengenapi tujuan Allah dalam hidupnya. Yusuf yang tadinya seorang remaja dari keluarga pengembala, berproses menjadi orang kedua paling berkuasa di sebuah negara adidaya serta paling maju peradabannya waktu itu dan di tempat itu juga Yusuf melihat mimpi yang Allah taruh tergenapi, melalui pintu masuk berupa menafsirkan mimpi Firaun sang penguasa dunia waktu itu. Penelitian ini berupaya mendalami makna tafsir Yusuf terhadap mimpi Firaun di Kejadian 41 dari bingkai kaum Pentakostal. Pemilihan metode kualitatif dengan pendekatan analisis teks dan kajian literatur diharapkan mampu memberikan penjelasan yang kuat, sistimatik, dan cermat terhadap kisah kehidupan Yusuf yang digambarkan Alkitab, analisis tafsir mimpi Firaun di Kejadian 41, dan pemaknaan dari bingkai kaum Pentakostal terkait kisah ini. Disimpulkan bahwa bagi kaum Pentakostal tafsir mimpi Firaun oleh Yusuf ini merupakan sebuah kisah yang menunjukkan bahwa Allah perancang maha sempurna, Yusuf yang menghidupi tujuan Tuhan, solusi ilahi, serta sarana Allah untuk mengenapi mengenapi tujuanNya dalam hidup Yusuf.